Independence of cyclic AMP and relA gene stimulation of glycogen synthesis in intact Escherichia coli cells. - Leckie, M P (1985)
Previous studies from our laboratory established that in Escherichia coli, glycogen synthesis is regulated by both the relA gene, which mediates the stringent response, and by cyclic AMP. However, those studies raised the question of whether this dual regulatory system functions in an independent or a dependent manner. We show here that this regulation is independent, i.e., each regulatory process can express its action in the absence of the other. Triggering the stringent response by amino acid starvation increased glycogen synthesis even in mutants lacking the ability to synthesize cyclic AMP or lacking cyclic AMP receptor protein; and cyclic AMP addition stimulated glycogen synthesis in relA mutant strains. We also show that physiological concentrations of GTP inhibit ADP-glucose synthetase (glucose-1-phosphate adenylyltransferase, EC 2.7.7.27), the rate-limiting enzyme of bacterial glycogen synthesis, in vitro. Because the stringent response is known to cause an abrupt decrease in the cellular level of GTP, modulation of ADP-glucose synthetase activity by this nucleotide could account for a substantial portion of the step-up in the cellular rate of glycogen synthesis observed when the stringent response is triggered.